Böndernas agerande inför och anpassning till storskiftet i sydvästra Finland - Laine, Kirsi (1700-tal: Nordic Journal for Eighteenth-Century Studies, 2021)
This article examines peasants’ goals and means of negotiation in the reallocation of land or enclosure reform called storskifte in the late eighteenth and early nineteenth century in Southwest Finland. It stresses the agency of peasants and their actions in the quest for best practices. The study is based on the meeting minutes of the storskifte reform of 230 villages with mainly freeholders or crown tenants as stakeholders. This article shows how peasants balanced between individualism and collectivism in their decision making because their goals were opposite. They aimed to increase the freedom of work and decision making in the household economy. At the same time, the cooperation with neighbours was an important method of decreasing the workload and costs of farming. Sources indicate that peasants made agreements with each other so they could combine both goals. They achieved independence as farmers as well as low costs by combining consolidation of land with mutual agreements about cooperation in specific issues, but they allowed each other to do individual decisions, too. This kind of flexible solution-seeking behaviour provides a new perspective on the discussion about peasants and agricultural change.
Keywords: peasants; enclosure; decision-making; household economy; agency; Finland